Management and change in turbulent times: How do Russian small business managers perceive the development of their business environment? - Jumpponen, Jari; Ikävalko, Markku; Pihkala, Timo (Journal of Business Economics and Management, 2008)
This paper focuses on the management of small businesses in Russia. Despite the growing importance of the Russian small business sector, there are surprisingly few empirical studies focusing on this topic. As the business environment in Russia is repeatedly noted to be in constant change, the purpose of the paper is to explore Russian owner‐managers perceptions of the development of their business environment from 2000 to 2004. The paper reports the results of a survey conducted among 164 business managers in North‐West Russia. The results indicate that Russian owner‐managers tend to monitor changes in the business environment and adapt their management accordingly, if not beforehand. However, the results are not unambiguous, as the study found wide variations in the extent to which gap the managers monitored and adapted to perceived changes in the business environment. First published online: 14 Oct 2010